ABO incompatibility: its impact on pregnancy and neonate - Nagashree, U.; P., Swetha; Manohar, Sumana; Parthasarathy, Latha Kanchi (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2019)
ABO incompatibility is one of the most common cause of haemolytic disease of fetus and new-born (HDFN). The expression of ABO incompatibility in most of the cases is mild due to the lower expression of A and B Antigens on fetal red cells. ABO incompatibility has affected the first pregnancy and is milder in the subsequent pregnancies. However, we describe this case with unusually severe form of ABO incompatibility which had an effect not only in her first pregnancy but also in all her subsequent pregnancies, evident as recurrent abortions and both her neonates developed pathological jaundice requiring exchange transfusion. It also emphasizes the fact that ABO incompatibility is not always a benign condition and should be considered in all babies whose mothers have O blood group, even in the presence of a negative DAT. Anticipation of ABO incompatibility not only in the first pregnancy but also in the subsequent pregnancies is necessary. Early diagnosis with cord blood bilirubin can prevent neonatal morbidity.